The Influence of Corporate Strategy, on Environmental Management Implications for Decision Making: A Survey of All Communities Affected by Landslides as Due to Environmental Damage in Nganjuk Regency - Sumantri, Siswo Hadi; Maarif, Syamsul; Yulianto, Bayu A.; Sutawijaya, Ahmad Hidayat (International Review of Management and Marketing, 2019)
The purpose of this study is to find out the effect of corporate strategy on the environmental management implications for decision making: a case study of landslides as a result of environmental damage in Nganjuk Regency. The results of the study show that the company strategy, the environmental management system implications for decision making which has characteristics possessed by someone to produce accurate decisions. Furthermore, it was found that the corporate strategy, the environmental management system implications for decision making. Keywords: Corporate Strategy, Environmental Management, Decision Making. JEL Classifications: M1, Q56 DOI: https://doi.org/10.32479/irmm.8552